Advances in Dye Removal Technologies - Mondal, Sourav (Green Chemistry and Sustainable Technology,, 2018)
This book describes the various advanced treatment methods for removal of multiple types of dyes from effluent stream. It pays particular attention to the economic aspects of treatment of textile waste-water. The different technologies illustrated in the book include adsorption, nanofiltration, advanced oxidation, micellar enhanced ultrafiltration, cloud-point extraction, and electrocoagulation. The book presents in-depth analyses of the removal mechanisms and performance optimization of the processes involved therein. This book will be useful to chemists, chemical engineers, environmental engineers, and health and pollution control professionals. The contents have been presented in a manner that they can be easily understood and applied by a wide variety of readers including researchers, students, and practicing engineers.